Copro-antigen capture ELISA for the detection of Teladorsagia (Ostertagia) circumcincta in sheep: improvement of specificity by heat treatment - Johnson, D.A.; Behnke, Jerzy M.; Coles, Gerald C. (Cambridge University Press, 2004)
A copro-antigen capture ELISA for the detection of Teladorsagia circumcincta infection in sheep was developed and evaluated. Experiments with faeces from worm-free sheep, that had been spiked with known concentrations of excretory-secretory (E–S) antigen indicated that a positive signal was generated with 180 ng of E–S/ml. A nested design, based on 8 infected and 8 worm-free sheep, was employed to assess the stages during sample preparation contributing to variation in signal from the assay. This showed that 87% of the variance in the optical density readings (ODs) was directly explained by infection status. Variation between individual sheep within infection groups, and between samples at various stages in the assay, collectively accounted for the remaining variance. Initial evaluation of specificity using faeces from animals carrying a range of monospecific infections indicated cross-reactivity with Haemonchus contortus and Nematodirus spathiger. However, by treating the supernatant from faeces for 20 min at 100°C, the cross-reactive signal was eliminated whilst the specific signal was largely preserved. Heat treatment of faeces from 12 non-infected sheep, 12 sheep with T. circumcincta and 6 with H. contortus resulted in sensitivity being increased from 66.7 to 85.7%, and specificity from 62.5 to 87.5%. OD values showed a significant positive relationship with adult worm burdens, although at low infection intensities there was some overlap between infected and worm-free animals. We discuss the application of CC-ELISAs in facilitating selective chemotherapy of sheep, as a means of avoiding the development of anthelmintic resistance in pastoral regions where sheep are farmed on a large scale.